Complete mitochondrial genome of the Korean crevice salamander (Karsenia koreana) (Amphibia, Urodela: Plethodontidae) - Jaejin Park; Woo-Jin Choi; Il-Hun Kim; Daesik Park (Mitochondrial DNA. Part B. Resources, 2019)
The Korean crevice salamander, Karsenia koreana, is the only known plethodontid salamander in Asia. In this study, we provide the first report of this salamander’s complete mitochondrial genome. The mitogenome had a length of 16,780 bp and consisted of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and 2 noncoding regions. The presented sequence may be highly useful for future phylogenetic and evolutionary studies of Plethodontidae.